EFISIENSI WAKTU PENDARATAN HASIL TANGKAPAN PURSE DI PELABUHAN PERIKANAN SAMUDERA (PPS) BELAWAN SUMATERA UTARA - Hutauruk, Tiara Nova Wulandari; Nelwida, Nelwida; Ramdhani, Farhan; Lisna, Lisna; Ramadan, Fauzan; Arfiana, BS Monica (Pena Akuatika : Jurnal Ilmiah Perikanan dan Kelautan, 2025)
The efficiency of fish landing time is an sign of determine the level of time management in fish landing activities as well as efforts to maintain the condition of quality and freshness of quality fish reaching consumers. The purpose of this study is to determine the efficiency of landing times and the factors that influence the efficiency of landing times of purse seine catches at the North Sumatra Province's Belawan Ocean Fisheries Port (PPS). This study employed a survey approach with a total sample size of 30 purse seine vessels. The efficiency level of landing time for purse seine catches at Belawan PPS is classified as efficient with an average of 75.89%. The results of the linear regression analysis obtained a value (R2) of 0.96 which shows that degree level of efficiency of fish landing time is influenced by 96% by the variables studied, namely (amount of catch (kg), number of unloaders (people), size of the fishing fleet (GT), the age of the unloader (years), and the experience of the unloader (years). And the remainder 4% is impacted by additional elements not covered in this research. Meanwhile, the variables that have a real influence are unloading time (minutes) having a value of 1,38×10−8 and wasted time (minutes) having a value of 8.85×10−16 significant < 0.05.